Avaliação da atividade da enzima ∆-aminolevulinato desidratase e parâmetros de estresse oxidativo em pacientes com diabetes mellitus tipo 2 - Bonfanti, Gabriela (2011)
Diabetes mellitus (DM) is a disorder of the metabolism of carbohydrates, lipids and proteins characterized by hyperglycemia, which in type 2 diabetes (T2DM) involves the production deficiency and / or insulin action. Diabetic subjects exhibit high levels of oxidative stress due to chronic and persistent hyperglycemia, which impairs the activity of the antioxidant defense system and promotes the generation of free radicals. This level of oxidative stress can cause renal, neurological, ocular and cardiovascular complications, such as systemic arterial hypertension (HAS). The enzyme δ-aminolevulinate dehydratase (δ-ALA-D) is a sulfhydryl enzyme, which participates in the synthesis of pyrrole compounds and has been linked to several diseases, including DM. The aim of this study was to evaluate the oxidative status of patients with DM2 and its relationship with the activity of the enzyme δ-ALA-D, lipid profile, body fat distribution besides the role of hypertension in the parameters analyzed. The results showed a decreased activity of the enzyme δ-ALA-D as well as an increase in its reactivation index in patients (n = 63) compared to controls (n = 63). It was also observed, in the T2DM group, an increased level of thiobarbituric acid reactive species (TBARS) and a smaller amount of antioxidants as vitamin C plasma protein thiol groups (P-SH) in plasma and nonprotein (NP-SH) in erythrocytes, as well as a reduction in activity of the enzyme catalase in erythrocytes. Patients who had DM2 plus hypertension (n = 30) showed a more pronounced decrease in the activity of δ-ALA-D than patients with type 2 diabetes only (n = 23) compared to healthy subjects (n = 30), along with an increased rate of reactivation. Also, patients DM2/HAS showed a greater depletion of NP-SH. Correlations among activity of δ-ALA-D and its reactivation index with oxidative stress markers, such as NP-SH and carbonyl groups, as well as lipid profile of patients were also observed. Further, correlations were found between the level of TBARS and triglycerides, as well as between vitamin C, plasma glucose and HbA1c as well as P-SH and body mass index. Therefore, patients with DM2 have changes in lipid profile and body fat distribution, and a situation of oxidative stress that can lead to changes in key molecules as the enzyme δ-ALA-D. This enzyme was effective in reflecting the level of oxidative stress of patients can be considered an interesting biomarker for assessment of damage in chronic metabolic processes such as DM. Furthermore, hypertension appears to be a synergistic factor to the metabolic condition of patients with type 2 diabetes, contributing to the development of its complications.